Peningkatan Potensi Anggota KWT dalam Pemanfaatan Pekarangan untuk Tanaman Obat dan Kosmetika Menggunakan Metode Tanam Vertikal di Desa Cibiru Wetan, Kabupaten Bandung - Widhya Aligita; Fauzan Zein Muttaqin; Soni Muhsinin; Ellin Febrina; Aiyi Asnawi (Jurnal Pengabdian Pada Masyarakat, 2019)
POTENTIAL DEVELOPMENT OF WOMAN FARMING GROUP IN THE UTILIZATION OF THE YARD FOR DRUG AND COSMETICS PLANTS USING VERTICAL GARDEN METHOD IN CIBIRU WETAN VILLAGE, BANDUNG REGENCY. The village of Cibiru Wetan is largely a rice field and swidden area with hilly contours and insufficient water availability. One of the utilization of fields with a lack of water is by growing plants that require minimal water, including medicinal plants and cosmetics. The initiation of this activity has a high prospect of success due to the high initiative and participation of the population in the form of women's farmer groups and the family welfare team as evidenced by the many achievements, awards, and skills gained by the Cibiru Wetan Village through the participation of its citizens. Therefore, the purpose of the project activity was socialization and practice at women’s farmer group of Cibiru Wetan Village through the use of medicinal plants and cosmetics with simple appropriate technology through vertical gardening. The method of implementation used in the training program for planting medicinal plants was divided two stage, that was providing information about family medicinal plants ranging from understanding to the benefits of the plants, and the last step was explaining or training and direct practice of planting medicinal plants and cosmetics using vertical planting. The results showed a positive understanding of the two groups of women’s farmer group I and II and the family welfare team, both for the stage of socialization and counseling as well as for the practice phase of planting medicinal plants and cosmetics vertically. The conclusion was the use of medicinal plants and cosmetics could increase the understanding of the target group and the compost produced by residents could be utilized through this activity.